Nutrient supplementation during the first 1000 days and growth of infants born to pregnant adolescents - Dewey, Kathryn G.; Matias, Susana L.; Mridha, Malay K.; Arnold, Charles D. (Annals of the New York Academy of Sciences, 2022)
This article was published in Annals of the New York Academy of Sciences [ © 2019 The Authors. Annals of the New York Academy of Sciences 25 published by Wiley Periodicals, Inc. on behalf of New York Academy of Sciences] and the definite version is available at: https://doi.org/10.1111/nyas.14191 The Journal's website is at: https://nyaspubs.onlinelibrary.wiley.com/doi/epdf/10.1111/nyas.14191